2018
DOI: 10.1038/s41467-018-04081-3
|View full text |Cite
|
Sign up to set email alerts
|

An enrichment method based on synergistic and reversible covalent interactions for large-scale analysis of glycoproteins

Abstract: Protein glycosylation is ubiquitous in biological systems and essential for cell survival. However, the heterogeneity of glycans and the low abundance of many glycoproteins complicate their global analysis. Chemical methods based on reversible covalent interactions between boronic acid and glycans have great potential to enrich glycopeptides, but the binding affinity is typically not strong enough to capture low-abundance species. Here, we develop a strategy using dendrimer-conjugated benzoboroxole to enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 69 publications
2
121
0
Order By: Relevance
“…We compared the glycopeptide and non-glycopeptide fractions in each parallel replicate, and showed that the specificity of our method is 55.4%. Our performance was better than the specificity of previously boronic acid and ZIC-HILIC enrichment method 8 . After N-glycan was released by the endoglycosidase, the core fucose was retained on the core GlcNAc residue, which allowed us to simultaneously distinguish the non-fucosylated and core fucosylated peptides.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…We compared the glycopeptide and non-glycopeptide fractions in each parallel replicate, and showed that the specificity of our method is 55.4%. Our performance was better than the specificity of previously boronic acid and ZIC-HILIC enrichment method 8 . After N-glycan was released by the endoglycosidase, the core fucose was retained on the core GlcNAc residue, which allowed us to simultaneously distinguish the non-fucosylated and core fucosylated peptides.…”
Section: Resultsmentioning
confidence: 54%
“…However, due to the low abundance of glycosylated peptides and the heterogeneity of glycan structures, N-glycopeptide enrichment is required. Several enrichment methods have been reported, including lectin 5 and hydrazide chemistry-based methods 6,7 , boronic acid enrichment 8 , hydrophilic interaction liquid chromatography (HILIC) 9 and metabolic labeling 10,11 . In general, these strategies for detecting N-linked glycosylated sites require an additional de-glycosylation step by N-glycosidase F (PNGase F) before MS detection 57 .…”
Section: Introductionmentioning
confidence: 99%
“…They later devised a boronic acid-based enrichment strategy to universally analyze glycoproteins, and identified 816 N-glycosylation sites from 332 glycoproteins in yeast. In a recent report, with more effective enrichment of glycopeptides, over 1,000 protein N-glycosylation sites were identified on over 500 proteins (Xiao et al, 2018c). Xiao et al (2016b) quantified the proteome and glycoproteome changes in yeast cells treated with tunicamycin compared with untreated cells.…”
Section: A Yeastmentioning
confidence: 99%
“…Strong interactions between boronic acid and glycans are critical to catch glycopeptides/proteins with low abundance. In order to enhance the interactions between boronic acid and glycans, different boronic acid derivatives were examined (Xiao et al, ). Among the derivatives tested, benzoboroxole was the most effective one, and it allowed us to identify the largest number of unique N‐glycopeptides from human whole cell lysates, as shown in Figure .…”
Section: Global Analysis Of Glycoproteinsmentioning
confidence: 99%
“…7,8 However, most of the existing methods rely on antibodies and uorescence probes to investigate individual proteins, which limit their capacities for large-scale analysis of protein degradation. In recent years, mass spectrometry (MS)-based proteomics has provided an opportunity to comprehensively characterize proteins, [9][10][11][12][13][14][15][16][17][18][19][20][21] including protein dynamics. [22][23][24][25] For instance, Doherty et al studied the stability of nearly 600 proteins in human A549 cells by using a dynamic stable isotope labeling by amino acids in cell culture (SILAC) approach.…”
Section: Introductionmentioning
confidence: 99%